2004
DOI: 10.1364/opex.12.000736
|View full text |Cite
|
Sign up to set email alerts
|

Origin of power fluctuations in GaN resonant-cavity light-emitting diodes

Abstract: Resonant-cavity light-emitting diodes (RCLEDs) with multiple InGaN/GaN quantum wells have been grown on sapphire substrates. The emission was through the substrate, and the top contact consisted of a highly reflecting Pd/Ag metallization. The peak emission wavelength was measured to be 490 nm. Under constant current biasing, the intensity was observed to fluctuate irregularly accompanied by correlated variations in the voltage. To investigate this further, emission from the RCLED was focused through a GaAs waf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…However, the optical central cavity thickness has been increased to , allowing for a thicker bottom cavity spacer layer as required for intracavity contact processing. It should also be noted that positioning the MQW close to the metal mirror, at the first antinode, results in the loss of the electroluminescence, attributed to diffusion of the metal into the MQW region [15]. Therefore, in a practical structure, the QWs must be placed at the second antinode from the mirror.…”
Section: Rcled Devicesmentioning
confidence: 99%
“…However, the optical central cavity thickness has been increased to , allowing for a thicker bottom cavity spacer layer as required for intracavity contact processing. It should also be noted that positioning the MQW close to the metal mirror, at the first antinode, results in the loss of the electroluminescence, attributed to diffusion of the metal into the MQW region [15]. Therefore, in a practical structure, the QWs must be placed at the second antinode from the mirror.…”
Section: Rcled Devicesmentioning
confidence: 99%
“…Evolution with time and change of current of nonuniform distribution of electroluminescence (EL) intensity on radiating surface of light-emitting diodes (LEDs) based on the ІnGaN/GaN and GaAsP/GaP heterostructures was already described by us [1,2] and many other researchers, for example in [3][4][5][6]. Active processes of defects formation and fluctuation in these heterostructures in excess of the density of direct current (J), which is specified by the manufacturer as maximal density of the direct current J max , impose the certain restrictions on their field of application, because EL intensity could be several times higher with J increase [1,2,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…To solve these problems, many physical mechanisms of the active processes, in particular, dynamics of defects development, transformation of functional parameters of LEDs and also their interrelation should be investigated [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Edge and mixed (screw/edge) dislocations in nitride materials act as nonradiative recombination centers and as conduits for charge transport resulting in leakage currents and breakdown (Amano et al, 2003;Davis et al, 2002). While high threading dislocation density is acceptable for light emitting diodes (LEDs) 6 -usually their small effect on the performance is attributed to the potential fluctuations related to the indium composition fluctuations (resulting from the poor In incorporation in the epitaxial layer during the growth or from the phase separation due to the large miscibility gap (I-hsiu & Stringfellow, 1996;Karpov, 1998;Korcak et al, 2007) ) observed in the active layers made from the ternary solid solution InGaN and in the corresponding QWs (Christen et al, 2003;Limb, 2007;Mukai et al, 2001) that provide the localization of carriers and reduce their in-plane diffusion to the non-radiative recombination centers -the high dislocation density, however, is fatal for laser diodes and power transistors; even for the LEDs including indium-free violet ones (Usikov et al, 2003) it leads to the drop in the efficiency and is the main factor of the device failure (Karpov, 2009;Roycroft et al, 2004 (Jain et al, 2000;Kukushkin et al, 2008;Miskys et al, 2003). Sapphire is a good choice for the nitride layers from the crystallographic point of view: crystal orientations of sapphire and gallium nitride grown on c-plane (0001) are parallel, with the unit cell of GaN being rotated by 30 • about c axis with respect to the unit cell of sapphire; the (1100) axis of GaN is parallel to the (1210) sapphire axis (Jain et al, 2000).…”
mentioning
confidence: 99%